A MICROSCOPIC TWO-CLUSTER MODEL OF PROCESSES IN 6Li - Kalzhigitov, N.; Takibayev, N.Zh.; Vasilevsky, V.S.; Akzhigitova, M.; Kurmangaliyeva, V.O. (Academic Scientific Journal of Computer Science, 2020)
Structure of bound and resonance states and dynamics of different processes in 6Li are investigated within a microscopic two-cluster model. The model is an algebraic version of the resonating group method which correctly treats the Pauli principle and makes use of the oscillator basis to expand a wave function of a two-cluster system. Within this model the nucleus 6Li is considered as two-cluster α + d system. Dynamics of the two-cluster system is totally governed by a semi-realistic nucleon-nucleon potential. We study interaction of 6Li with electrons and photons. Form factors of elastic scattering of electron are determined for two nucleon-nucleon potentials. We also study the density distribution of protons and neutrons in 6Li. We demonstrate that the model used correctly reproduces form factors for the ground state of 6Li. Our results are compatible with results of other microscopic models. The capture reaction α + d = 6Li + γ are investigated in detail. The astrophysical S-factor of the reaction is obtained at low-energy region.